A Study on Environmental, Social and Governance Fund Performance and Fund Flow: Evidence From Korea Stock Exchange - Kwak, Dongchul; Kim, Yu Kyum; Kwon, Il Sook (Frontiers in Psychology, 2022)
This study analyzed the sensitivity between fund flow and fund performance with Korean funds, whether there would be a difference in the sensitivity between ESG funds and non-ESG funds, and whether there was a difference in sensitivity according to the type of past fund performance (positive, negative). The main results of the analysis are as follows. Firstly, the analysis of the fund flow-performance correlation of Korean funds revealed that they had a negative (-) correlation and the ESG did not affect fund flow. Analysis of the difference in sensitivity between fund flow and performance volatility revealed that there was a negative (-) correlation regardless of the performance measuring method and ESG. Lastly, the comparison of fund flow and performance sensitivity according to the type of past fund performance revealed that despite consistent asymmetry, there was little difference in sensitivity asymmetry between ESG funds and non-ESG funds. The results reveal that, unlike the expectation that investors in Korean ESG funds would focus more on non-financial properties like the purpose of investment than on profit, they attach the same importance to fund performance.